2009
DOI: 10.1002/cbdv.200700450
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolites in Bryophytes: An Ecological Aspect

Abstract: Bryophytes frequently grow in an unfavorable environment as the earliest land plants, and inevitably biosynthesize secondary metabolites against biotic or abiotic stress. They not only defend against the plant competition, microbial attack, and insect or animal predation, but also function in UV protection, drought tolerance, and freezing survival. This review covers the ecological aspect of secondary metabolites in bryophytes and is taxonomically presented according to the ecological significances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 55 publications
1
96
1
2
Order By: Relevance
“…Contrary to the hypothesis of bryophytes being unpalatable to herbivores due to their chemical defences, with many secondary metabolites functioning to protect against herbivory, and their consideration as nutrient-poor plants for herbivores (Glime, 2006;Cornelissen et al, 2007;Xie & Lou, 2009), our results suggest that there is frequent, although low magnitude, herbivory in two mosses present in the understory of a tropical rainforest. The total values and mean number of injured plants, as well as the index of damage, were higher in H. tamarisci than in L. concinnum, indicating that H. tamarisci was more favoured by herbivores.…”
Section: Discussioncontrasting
confidence: 85%
“…Contrary to the hypothesis of bryophytes being unpalatable to herbivores due to their chemical defences, with many secondary metabolites functioning to protect against herbivory, and their consideration as nutrient-poor plants for herbivores (Glime, 2006;Cornelissen et al, 2007;Xie & Lou, 2009), our results suggest that there is frequent, although low magnitude, herbivory in two mosses present in the understory of a tropical rainforest. The total values and mean number of injured plants, as well as the index of damage, were higher in H. tamarisci than in L. concinnum, indicating that H. tamarisci was more favoured by herbivores.…”
Section: Discussioncontrasting
confidence: 85%
“…This sample is nearly 8000 cal yr BP old, but we would have expected bryophytes to be present earlier in the record. The apparently low preservation potential of bryophyte DNA could be linked to the high production of secondary metabolites in bryophytes (Xie and Lou, 2009), which enhance DNA degradation. Vascular plant DNA on the other hand was found down to the bottom of the core, albeit with low diversity.…”
Section: Dna-based Paleoenvironmental History Of Bliss Lake and Surromentioning
confidence: 99%
“…Both the plants show substantial antimicrobial activity and clear zone of inhibition were seen (Plate 1). However, the comparatice results showed that H. involuta was found more active against all the three bacterial strains even at lower concentration (10mg/mL), indicating that more quantity of secondary metabolites and elevated antioxidant enzymatic activity are the possible reasons for this enhanced inhibitory response (Xie and Lou, 2009). …”
Section: Resultsmentioning
confidence: 94%